Analysis of COVID-19 information problems in the Special Region of Yogyakarta - Salsa, Khalda; Fajri , Choirul; Farihanto , Muhammad Najih; Tawar, Tawar (Universitas Ahmad Dahlan, 2023)
This study aims to reveal the problematic information on Covid-19 that occurred in the Special Region of Yogyakarta. The method used in this research is a case study qualitative approach. While the paradigm used is the interpretive paradigm. The results found that a lot of hoax information was found scattered in the community and there were still many difficulties in the coordination flow and the emergence of miscommunication in the DIY Government in the process of distributing information.